Implikasi Hukum Paris Agreement Melalui Program REDD+ Berbasis Blue Carbon Di Indonesia - Sofia, Elda (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
To replace the Kyoto Protocol to the UNFCCC post-2020 the Participating Countries of UNFCCC made a new commitment namely Paris Agreement to the UNFCCC. Indonesia has ratified the Paris Agreement to become its national law. In Paris Agreement to the UNFCCC, all Countries should reduce greenhouse gas/GHG emissions following the principle of common but differentiated responsibilities. GHG emissions reductions obligations are set out in a nationally determined contribution/NDC. Within the NDC, Indonesia achieves emission reduction greenhouse gas targets up to 29% on its own and up 41% with international assistance. GHG emissions reductions through the forestry sectors are key sectors in NDC Indonesia at 17.2%. Using the method of normative research through an approach to legislation. After ratified of Paris Agreement to the UNFCCC brings legal implications for Indonesia namely the establishment of the laws on REDD+ in the forestry sector. Efforts made by the government of Indonesia is the establishment of the laws on REDD+. It has found the legal problem which can be a factor inhibiting the achievement of NDC target consisting of law enforcement, legal certainty of forest area. It is suggested that the Government of Indonesia makes regulation on mangrove forest. Untuk menggantikan Kyoto Protocol pasca 2020 Negara Peserta UNFCCC membuat komitmen baru yaitu Paris Agreement to the UNFCCC. Indonesia telah meratifikasi Paris Agreement menjadi hukum nasional. Di dalam Paris Agreement to the UNFCCC, semua negara diberikan kewajiban untuk mengurangi emisi gas rumah kaca sesuai dengan prinsip common but differentiated responsibilities. Kewajiban pengurangan emisi gas rumah kaca ditetapkan dalam nationally determined contribution/NDC. Di dalam NDC, Indonesia mempunyai target untuk mengurangi emisi gas rumah kaca sebesar 29% dengan usaha sendiri dan sampai dengan 41% dengan bantuan internasional. Pengurangan emisi gas rumah kaca melalui sektor kehutanan adalah sektor utama dalam NDC Indonesia yaitu sebesar 17.2%. Metode penelitian yang digunakan adalah penelitian hukum normatif yaitu melalui pendekatan perundang-undangan. Pasca diratifikasinya Paris Agreement to the UNFCCC membawa implikasi hukum bagi Indonesia yaitu dibentuknya sejumlah peraturan-peraturan terkait REDD+ di sektor kehutanan. Upaya-upaya yang dilakukan pemerintah Indonesia untuk mengimplementasikan Paris Agreement to the UNFCCC sektor kehutanan adalah membentuk sejumlah peraturan-peraturan hukum terkait REDD+. Persoalan-persoalan hukum yang ditemui menjadi faktor penghambat tercapainya target NDC Indonesia yaitu penegakan hukum, kepastian hukum kawasan hutan. Disarankan agar dibentuknya regulasi tentang perlindungan terhadap hutan mangrove.